Effect of axial length and anterior chamber depth on the peripheral refraction profile - Masoud Khorrami-Nejad; Raha Moradi; Alireza Akbarzadeh Baghban; Bahram Khosravi (International Journal of Ophthalmology, 2021)
AIM: To evaluate the effect of axial length (AL) and anterior chamber depth (ACD) on peripheral refractive profile in myopic patients compared to emmetropic participants. METHODS: This cross-sectional study was conducted in right eyes of 58 participants of whom 38 were emmetropic and 20 were myopic. Central and peripheral refraction were measured at 10°, 20°, and 30° eccentricities in nasal and temporal fields using an open-field autorefractor. The Lenstar LS900 was used to measure ACD and AL. The participants were divided into three groups of short (<22.5 mm), normal (22.5-24.5 mm), and long eye (>24.5 mm) according to AL and three groups of low ACD (<3.00 mm), normal ACD (3.00-3.60 mm), and high ACD (>3.60 mm) according to ACD. RESULTS: The mean age of the participants was 22.26±3.09y (range 18-30y). The peripheral mean spherical refractive error showed a hypermetropic shift in myopic and emmetropic groups although this shift was more pronounced in the myopic group. The results showed significant changes in the spherical equivalent, J0, and J45 astigmatism in all gazes with an increase in eccentricity (P<0.001). The pattern of refractive error changes was more noticeable in long and short eyes versus normal AL eyes. Moreover, the pattern of peripheral refractive changes was much more prominent in the high ACD group versus the normal ACD group and in the normal ACD group versus the low ACD group. CONCLUSION: Peripheral refraction changes are greater in participants with AL values outside the normal range and deeper ACD values compared to participants with normal AL and ACD.